Avaliação integrada do pré-tratamento do farelo de arroz desengordurado com solventes eutéticos e posterior hidrólise com água subcrítica - Moreira, Bárbara Pezzini (2022)
In this dissertation, defatted rice bran was subjected to pre-treatments with deep eutectic solvents aiming at delignification and enrichment in carbohydrate content. The biomass was completely characterized. Four mixtures of eutectic solvents were evaluated: Choline Chloride: Glycerol, Choline Chloride: Glycerol with water, Choline Chloride: Urea and Choline Chloride: Urea with water. Changes in functional groups related to cellulose and hemicelluloses were evaluated for pretreatments at 120 °C with a 1:10 biomass/eutectic solvent ratio at 2, 4 and 6h using Fourier transform infrared spectrophotometry (FT-IR). For the pre-treatments with the 4 mixtures of eutectic solvents, the best time was 4 hours. Thermogravimetric analysis (TGA) of the remaining solid indicated that the highest degree of delignification (2.5-fold reduction) and the highest hemicellulose content (44.1%) was obtained with the mixture of Choline Chloride: Urea with water. However, preliminary essays showed that the use of this operational sample for further analysis was unfeasible. Thus, the most suitable eutectic solvent for pretreatment was the one formed by Choline Chloride:Glycerol, which generated a degree of delignification of 1.3 times, showed a change in cellulose content from 27.8% to 11.3 % and increased the hemicellulose content from 11.6% to 40.1%, when comparing the in natura and pre-treated samples. Subcritical hydrolysis was carried out in a reactor in semi-continuous mode. The process variables evaluated were the temperature (230 and 260 °C) and the mass ratio between solvent/feed (R50 and R-100). The total reaction time was 20 min in a fixed pressure of 10 MPa. The highest yield of fermentable sugars (14.37 ± 1.12 g/100 g of biomass) was obtained at 260 °C /R-100 for the defatted rice bran samples pre-treated with the solvent Choline Chloride:Glycerol. The defatted rice bran submitted to pre-treatment showed a yield of sugars 2.20 times higher compared to in natura samples.